Time lags in reporting of biological invasions: the case of Mediterranean Sea - ZENETOS, ARGYRO; GRATSIA, EIRINI; CARDOSO, ANA-CRISTINA; TSIAMIS, KONSTANTINOS (Mediterranean Marine Science, 2019)
Time lags in non-indigenous species (NIS) reporting can create uncertainty in the analysis of NIS introduction rates, which can lead to inadequate actions, prevention measures and their evaluation. The present study aims to highlight time lags in marine NIS reporting in the Mediterranean Sea, i.e.: the time that mediates from the detection of a new NIS in the Mediterranean Sea until its publication. Our results revealed that the time lag in NIS reporting in the Mediterranean Sea has been considerably decreased during the last decades. There is also a noticeable difference in the time lag of reporting NIS in association with the taxonomic group of the species. Fish have generally shorter time lags in their reporting when compared with other taxonomic groups (e.g. macrophytes, Annelida, Bryozoa). Considering the widespread concern on marine introductions, it is essential to recognize the importance of taking into account time lags of reporting NIS that skew introduction patterns of marine NIS, permitting thus more accurate management assessments.